1985
DOI: 10.1111/j.1530-0277.1985.tb05530.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Recovery in Male Alcoholics' Neuropsychological Performance One Year after Treatment

Abstract: Thirty-seven middle-aged alcoholics and 20 nonalcoholic controls equated for age and education were examined on measures of verbal, learning/memory, abstracting/problem-solving, and perceptual-motor abilities 7 weeks after beginning detoxification and 13 months later. At 7 weeks, the alcoholics were significantly different from the controls on the verbal, abstracting/problem-solving, and perceptual-motor clusters and tended to differ on the learning/memory tests. At 13 months, the same pattern of differences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
3

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 24 publications
5
48
3
Order By: Relevance
“…Several studies have shown persisting cognitive deficits in alcoholics who remained abstinent for 1 to 5 years (Brandt, Butters, Ryan, & Bayog, 1983;Fabian & Parsons, 1983;Grant, 1987;Yohman, Parsons, & Leber, 1985) while others have found minimal cognitive impairments in alcoholics with shorter durations of abstinence (Eckardt et al, 1995). These findings have led to speculation that cognitive deficits following the acute phase of withdrawal may be relatively static (Grant, Adams, & Reed, 1984;Goldman, 1986;Grant, Unkenstein, & Bowden, 1991).…”
mentioning
confidence: 97%
“…Several studies have shown persisting cognitive deficits in alcoholics who remained abstinent for 1 to 5 years (Brandt, Butters, Ryan, & Bayog, 1983;Fabian & Parsons, 1983;Grant, 1987;Yohman, Parsons, & Leber, 1985) while others have found minimal cognitive impairments in alcoholics with shorter durations of abstinence (Eckardt et al, 1995). These findings have led to speculation that cognitive deficits following the acute phase of withdrawal may be relatively static (Grant, Adams, & Reed, 1984;Goldman, 1986;Grant, Unkenstein, & Bowden, 1991).…”
mentioning
confidence: 97%
“…Sullivan Leber, Jenkins, & Parsons, 1981;Mann, Gunther, Stetter, & Ackermann, 1999;Pitel et al, 2009;Rosenbloom et al, 2004;Rourke & Grant, 1999;Yohman, Parsons, & Leber, 1985) (for reviews, see Oscar-Berman et al, 2014;Pitel, Eustache, & Beaunieux, 2014). Remaining to be established are parameters of recovery, including length of sobriety, age at alcoholism initiation, age at testing, style of drinking, concomitant nutritional deficiencies and non-alcohol drug use, sex, physiological, ethnic, and genetic characteristics of alcoholics (Stavro et al, 2013).…”
Section: Recovery Of Component Processes Of Memory Functions With Alcmentioning
confidence: 99%
“…Although there is evidence of cognitive recovery in IQ, verbal skills and recent memory following 1 or 2 weeks of abstinence [8,9] , residual deficits have been found in 45% of patients 3 weeks into abstinence [10] . Sustained impairments have been found in problemsolving visuospatial ability and perceptual motor skills [11,12] after 4 weeks of abstinence, with some deficits persisting after a year of abstinence [13,14] .…”
Section: Introductionmentioning
confidence: 99%